The Level of Human Resource Talent Management in Jordanian Private Universities in the Digital Age - Abujame, Ibrahim Ahmad; banat, Sana Yaqoub; Wahba, Fatima AbdAlKaerrm (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the management of human resources talents in private Jordanian universities. The study employed the descriptive approach; to achieve its objectives, a self-administered questionnaire was designed consisted of (38) items distributed on four dimensions and an open question. Both validity and reliability of the questionnaire were secured and verified. A purposeful study sample was (376), out of them only (310) responded to the questionnaire. The results of the study showed that the level of application of human resource talent management in private universities for all dimensions of the questionnaire was medium (3.13). The level of the dimension of recruitment was (3.35) at a medium level, the dimension of professional development was (3.17) at a medium level, the dimension of discovery was (3.09) with a medium level, and the dimension of talent retention was (2.93) with a medium level. While the results of the open question showed that the most important suggestion was to enhance the effectiveness of talent management was the establishment of an official organized talent management (54.2%), while the suggestion to view the experiences of leading universities in talent management and exchange them was as the lowest suggestion (1.39%). The study recommended the need to find departments concerned with the gifted within the university campus, and to establish an integrated unit for talent management entrusted with the tasks of attracting, discovering, professional development, and retaining talents, allocating appropriate financial resources to them, and developing strategic plans and appropriate regulations that contribute to organizing the process of selecting and employing academic talents. Involving the talented faculty member in the development processes and setting his own performance improvement programs, and investing distinguished academic talents through exchanging them between Jordanian universities and lending them to emerging universities to participate in their development.